THE ROLE OF ENTREPRENEURSHIP COMPETENCE, ENTREPRENEURSHIP ORIENTATION AND KNOWLEDGE MANAGEMENT ON MSME PERFORMANCE - Hariroh, Fiqih Maria Rabiatul; Kosim, Muhammad (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
This study aimed to determine the role of entrepreneurial competence in the effect of entrepreneurial orientation on MSME performance. This study uses a quantitative approach. The data used in this study is primary data based on questionnaires given to 100 business actors as respondents. The analyzer uses Smart PLS. The results of this study are that the entrepreneurial orientation variable influences the performance of MSME. There is no influence of the knowledge management variable on the performance of MSME. Then entrepreneurial orientation and knowledge management directly show an effect on entrepreneurial competence. Furthermore, the competency variable has a positive and significant influence as a mediating variable on the entrepreneurial orientation variable on MSME performance. As well as the competence variable has a positive and considerable influence as a mediating variable on the knowledge management variable on MSME performance.